Is the FCI Effective as the Police Strategy in Interrogation? - Muthi’ah, Nadhirah; Setia, Eddy; Rangkuti, Rahmadsyah (JOALL (Journal of Applied Linguistics and Literature), 2024)
The politeness, dignity, serenity, and tranquillity should be reflected by the investigator without violence during the interrogation process. This study aims to identify the Forensic Conversational Implicature (FCI) found in a police interrogation of a murder case. A qualitative method with a philosophical approach was used, and Forensic Discourse Analysis was used as an analytical framework. A documentation study method was used to collect the data in the form of an interrogation video obtained from the Explore with Us YouTube channel. Utterances that are indicated as implicature are the data taken from the interrogation video, particularly in murder cases that happened in the U.S. In analyzing the data, deductive content analysis was applied. The results show that two types of FCI are found in this study, with particularized conversational implicature as the most dominant since it requires certain background knowledge and context to understand the investigator’s utterances. Meanwhile, generalized took second place as it does not require specific context knowledge to determine the additional conveyed meaning of several investigators’ utterances. Moreover, the reasons behind the realization of CI are under two themes, namely, gaining trust and humanity.